L’origine resta futuro. La questione dell’affettività nel corso heideggeriano sui Concetti fondamentali della filosofia aristotelica (1924) - Caputo, Annalisa (Bollettino Filosofico, 2020)
This paper reconstructs the origin and choice of the term Befindlichkeit, analyzing the Heideggerian course Fundamental Concepts of Aristotelian Philosophy (1924). In the first step, the importance of the question is motivated within the Heidegger path. Later, philological aspects are addressed, showing how the term Befindlichkeit is coined as a translation of three different Greek terms (diathesis, pathos, hedone) and then acquires autonomous thickness, to indicate the emotional situation of Dasein. Finally, we focus on what could be called “the pathe of authenticity”: eudaimonia (i.e. the telos) and phobos (necessary for an authentic decision): emotional tonalities that seem one of the most interesting deliveries of the Heideggerian scenario. Keywords: Aristotle, Befindlichkeit, Emotional Tonalities, Heidegger, Pathos